Type 2 diabetes mortality at Mexican borders - Manzanares Rivera, José Luis (2016)
Objective: To analyze type II diabetes mortality rates geographic distribution and evolution in time across both Mexican border regions during the period 1998-2013. Methods: The work is based on exploratory and inferential data analysis conducted using death reports from the national health information system. The analysis considers social determinants of health as a theoretical paradigm and includes microdata on consumption patterns at household level for the US-Mexico and Mexico-Guatemala border states. Results: A convergence path for type II diabetes mortality rates is found during the last 15 years between the studied border regions. Conclusions: The evidence presented indicates that the southern border states had been experiencing an epidemiologic transition towards mortality causes such as type II diabetes in the last decade. A trajectory that reflects a convergence pattern towards mortality rates found in the northern border states.